Lactose tolerance test on Indonesian newborn infants - Achmad Surjono; Surjantoro Surjantoro; Tonny Sadjimin; Ismangun Ismangun (Paediatrica Indonesiana, 1973)
It is well accepted that milk is the only source of nutrition for newborn infants. Human milk as well as cow's milk contains a considerable amount of specific carbohydrate, namely lactose. Lactose must be hydrolyzed into its components monosaccharides, glucose and galactose by small intestinal enzyme lactase in order to be utilized.